2018
DOI: 10.1038/s41374-018-0055-2
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular fractal dimension predicts prognosis and response to chemotherapy in glioblastoma: an automatic image analysis study

Abstract: The microvascular profile has been included in the WHO glioma grading criteria. Nevertheless, microvessels in gliomas of the same WHO grade, e.g., WHO IV glioblastoma (GBM), exhibit heterogeneous and polymorphic morphology, whose possible clinical significance remains to be determined. In this study, we employed a fractal geometry-derived parameter, microvascular fractal dimension (mvFD), to quantify microvessel complexity and developed a home-made macro in Image J software to automatically determine mvFD from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 55 publications
5
12
2
Order By: Relevance
“…Fractal dimension measures the complexity of structures. In our study, a significant increase of mvFD was found in malignant breast lesions, indicating that malignant lesions have more dense, irregularly branched and twisted microvessel structures, which is consistent with the findings of other studies on oral cancer [ 45 ], renal cell carcinoma [ 19 ] and glioblastoma [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…Fractal dimension measures the complexity of structures. In our study, a significant increase of mvFD was found in malignant breast lesions, indicating that malignant lesions have more dense, irregularly branched and twisted microvessel structures, which is consistent with the findings of other studies on oral cancer [ 45 ], renal cell carcinoma [ 19 ] and glioblastoma [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…Pericytes represent a specialized mesenchymal cell type within the tumor perivascular niche and potentiates tumor vascular functions, tumor metastasis and immune cell infiltration. 9 , 30 32 Pericytes in GBMs exhibit excessive outgrowth 33 and are pivotal for maintaining the integrity of the BTB. 10 In this study, we reveal that pericytes directly interact with GBM cells residing in the perivascular niche to enhance DNA repair and induce TMZ chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological parameters [ 20 , 29 ], including number of vessel ( NV ), number of branch points ( NB ), vessel density ( VD ), vessel diameter ( D ) and distance metric ( τ ), were measured. Moreover, four new parameters, microvessel fractal dimension ( mvFD ) [ 29 – 31 ]. Murray’s deviation ( MD ) [ 29 , 32 34 ], bifurcation angle ( BA ) [ 29 , 35 – 37 ], and spatial vascular pattern ( SVP ) [ 29 , 38 ], calculated by vessel density ratio ( VDR ) [ 29 , 32 , 34 , 39 ], were also extracted from the HDMI image for characterizing the tumor microvessels.…”
Section: Methodsmentioning
confidence: 99%